Hollow nanogold/meso-magnetite composite: pulsed laser synthesis, properties, and biosensing application - Chaudhari, Nilima; Warule, Sambhaji; Agrawal, Shailaja; Thakare, Vishal; Jouen, Samuel; Hannoyer, Beatrice; Kale, Bharat; Paknikar, Kishore; Ogale, Satishchandra B. (Journal of Nanoparticle Research, 2013)
A facile and template-free UV (Excimer) laser photolysis process is demonstrated to transform a Fe-complex into unique hollow Fe3O4 nanosphere morphology with each sphere having nanometric pores and an opening. Depending on the Fe-complex concentration and processing time interesting configurations are seen to evolve. When an identical process is applied to a mixture of Fe-complex and chloroauric acid an enthrallingly decorated Au-Fe3O4 nanostructure evolves, with Au nanoparticles surface-loaded on mesospheric Fe3O4. This room temperature process implemented under normal laboratory conditions is clearly versatile and applicable to heterojunction nanomaterials synthesis in a single-step process. The potential application of these gold-decorated magnetic nanostructures was also investigated for immuno-magnetic capture of E. coli in biosensing and these were found to be sensitive even below 1,000 cfu/ml. The test results demonstrate linear sensing response in the range of 10(3)-10(5) cfu/ml. We also show that these nanostructures can be used for simple electrical conductivity-based biosensing since they show dramatic conductivity change in a simple drop-cast test. A new laser-based approach to the synthesis of unique hollow sphere morphology of magnetite (Fe3O4) without and with Au nanoparticle decoration is presented. The potential application of these gold-decorated magnetic nanostructures was also investigated for immuno-magnetic capture of E. coli in biosensing and these were found to be sensitive even below 1,000 cfu/ml.
Keywords: E. coli cells; Fe-complex; Meso-magnetite; Nanobiotechnology; Nanocomposite; Pulse laser irradiation

High surface area porous carbon for ultracapacitor application by pyrolysis of polystyrene containing pendant carboxylic acid groups prepared via click chemistry - Chhatre, Shraddha; Aravindan, Vanchiappan; Puthusseri, Dhanya; Banerjee, Abhik; Madhavi, Srinivasan; Wadgaonkar, Prakash P.; Ogale, Satishchandra B. (Materials Today Communications, 2015)

Hysteretic DC electrowetting by field-induced nano-structurations on polystyrene films - Sawane, Yogesh B.; Datar, Suwarna; Ogale, Satishchandra B.; Banpurkar, Arun G. (Soft Matter, 2015)
Electrowetting (EW) offers executive wetting control of conductive liquids on several polymer surfaces. We report a peculiar electrowetting response for aqueous drops on a polystyrene (PS) dielectric surface in the presence of silicone oil. After the first direct current (DC) voltage cycle, the droplet failed to regain Young's angle, yielding contact angle hysteresis, which is close to a value found in ambient air. We conjecture that the hysteretic EW response appears from in situ surface modification using electric field induced water-ion contact with PS surface inducing nano-structuration by electro-hydrodynamic (EHD) instability. Atomic force microscopy confirms the formation of nano-structuration on the electrowetted surface. The effects of molecular weight, applied electric field, water conductivity and pH on nano-structuration are studied. Finally, the EW based nano-structuration on PS surface is used for the enhanced loading of aqueous dyes on hydrophobic surfaces.

Hexaphosphate-derived phosphorus-functionalized carbon for lithium-ion battery anode - Gawli, Yogesh; Wahid, Malik; Fernandez, Rohan; Kothari, Dushyant; Shelke, Manjusha; Ogale, Satishchandra B. (Chemistryselect, 2017)
We show that high-temperature annealing of a dried hexaphosphate, namely phytic acid, renders activated (micro-porous) and phosphorus-functionalized graphene like carbon in a one-step process. At high enough temperature few volatile phosphates serve as porogen-forming entities while other groups reactively functionalize the carbon surface. The optimized material has high effective surface area due to the presence of defect states. As an anode material for Li-ion battery, it exhibits a reversible capacity that is double that of the graphite and is stable for 1000 cycles even at a high current of 5 A g(-1). This result is attributed to the concurrent presence of micropores and phosphorus containing groups in the carbon matrix.

High quality hybrid perovskite semiconductor thin films with remarkably enhanced luminescence and defect suppression via quaternary alkyl ammonium salt based treatment - Naphade, Rounak A.; Zhao, Baodan; Richter, Johannes M.; Booker, Edward; Krishnamurthy, Shrreya; Friend, Richard H.; Sadhanala, Aditya; Ogale, Satishchandra B. (Advanced Materials Interfaces, 2017)
Significant enhancement in the luminescence and superior photophysical properties of CH3NH3PbBr3 thin films prepared via simple single step spin coating process involving a novel additive mediated solvent extraction step is reported. This process results in significantly lower disorder in CH3NH3PbBr3 perovskites with Urbach energies reducing from ≈35 to ≈17 meV, which is the lowest reported value to date. The additive mediated process also results in a remarkable improvement in the photoluminescence quantum yields (PLQYs) from 1% to 30%. Coupled with the overall increase in surface roughness, a significant increase in the internal PLQY from 7% to 77% is estimated, indicating the superior quality of the treated thin films. The resultant high quality CH3NH3PbBr3 perovskites with remarkable photophysical properties can be used in realizing highly efficient optoelectronic devices. Highly efficient light emitting diodes using these perovskites are demonstrated here.